Estimasi Sumberdaya Batubara Seam C1 Menggunakan Metode Ordinary Kriging Pada Pit Central Timur PT. Allied Indo Coal Jaya Sawahlunto - Andrian Eka Putra; Adree Octova (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract. PT. Allied Indo Coal Jaya (PT. AICJ) is a coal mining company located in Swahlunto City, West Sumatera Province, Indonesia. PT. AICJ is currently opening a new pit, Pit Central Timur, which is located next to Pit Central Barat. Before starting coal mining activities, an estimate of coal resources is needed. This process aims to estimate the amount of coal tonnage and how the coal deposits spread below. In this research, the method used to estimate coal resources is ordinary kriging method. Coal seam that will be estimated in this research is seam C1. From the estimation results using this ordinary kriging method, later the sediment model from coal will be obtained among with the amount of coal tonnage. The total coal tonnage in the research area was 1.943.370 tonnes, with overburden 7.312.500 bcm. From the calculations also we got stripping ratio 3,76 bcm/tonne.Keywords: Resources, Estimation, Ordinary Kriging, Variogram, Blok Model